Classification of argentine maize landraces in heterotic groups - Delucchi, Carla (2012)
The genetic diversity of maize (Zea mays L) is a valuable and strategic natural resource that plays a key role in the breeding progress. However, exploitation of genetic variability from landraces has not reached a significant level of utilization in breeding programs in Argentina yet. In order to establish their breeding potential, the best 15 out of a group of about 300 landraces from Argentina, were evaluated for various agronomic characters in testcrosses with five lines representing different heterotic groups. Testcrosses were evaluated in nine environments during two growing seasons. A factorial array of those landraces and tester lines was used. Differences for landraces, testers, and landrace x tester interactions were detected for ear diameter and length, ear attachment and plant height, and grain yield. Yield data were further analyzed following additive main effects (landrace and tester) and multiplicative interaction (landrace x tester) models. The first two principal components were significant and accounted for 67% of that interaction. The first axis was consistent with the Argentine flint vs. US dent (Mo17), and US dent (B73) vs. US dent (Mo17) heterotic patterns. The second axis exhibited a contrast between Argentine flint and US dent (B73 or B73 derived line) heterotic groups. The first two principal components of the landrace x tester interaction and mean performance of testcrosses were considered to identify eight landraces as parents of three composite populations.